ETHNIC NATIONALITIES AND THE CHALLENGE OF NATIONAL INTEGRATION IN POST-COLONIAL NIGERIA (LAPAI JOURNAL OF NIGERIA HISTORY, 2023)
Nigeria’s independence in 1960 brought hope for nation-building and accelerated development to her people. However, this expectation remained elusive due to the inability to evolve a strong united entity (nation) out of the conglomeration of groups in the country. National integration constitutes a major challenge in Nigeria’s nation-building and quest for development. The 1914British amalgamation brought peoples of different socio-cultural, economic and political backgrounds together. The British conducted this exercise for its colonial convenience without consideration for the diversity of the people. Indeed, the British geared their colonial policies towards satisfying the needs of the loose federation. Therefore, after independence, the challenge of national integration became more manifest in Nigeria, as characterized by mutual suspicion, ethnic and inter-tribal clashes, religious crises, political unrest and the pursuit of ethnic interests. This study examines the dynamics of Nigeria’s heterogeneity, the challenge of integration and the prospects of turning the country’s diversity into strength. A historical research method, comprising the use of primary and secondary sources, was employed. The study identifies some of the hindrances to national integration in Nigeria including the triumph of ethnic nationalism, continuous domination and marginalisation of minority groups, and ethnic, religious and political crises, all stemming from the country’s weak federal system. The study recommends a sovereign national conference to strengthen Nigeria’s federalism and the reinvigoration of the nation's integrating apparatuses.